Formulation matters! A spectroscopic and molecular dynamics investigation on the peptide CIGB552 as itself and in its therapeutical formulation. (10th June 2021) - Savioli, Marco; Antonelli, Lorenzo; Bocchinfuso, Gianfranco; Cavalieri, Francesca; Cimino, Rita; Gatto, Emanuela; Placidi, Ernesto; Fernandez Masso, Julio Raul; Garay Perez, Hilda; Santana, Hector; Guerra‐Vallespi, Maribel; Venanzi, Mariano
Abstract : Synthetic therapeutic peptides (STP) are intensively studied as new‐generation drugs, characterized by high purity, biocompatibility, selectivity and stereochemical control. However, most of the studies are focussed on the bioactivity of STP without considering how the formulation actually used for therapy administration could alter the physico‐chemical properties of the active principle. The aggregation properties of a 20‐mer STP (Ac‐His‐Ala‐Arg‐Ile‐Lys‐D‐Pro‐Thr‐Phe‐Arg‐Arg‐D‐Leu‐Lys‐Trp‐Lys‐Tyr‐Lys‐Gly‐Lys‐Phe‐Trp‐NH2 ), showing antitumor activity, were investigated by optical spectroscopy and atomic force microscopy imaging, as itself (CIGB552) and in its therapeutic formulation (CIGB552TF). It has found that the therapeutic formulation deeply affects the aggregation properties of the investigated peptide and the morphology of the aggregates formed on mica by deposition of CIGB552 and CIGB552TF millimolar solutions. Molecular dynamics simulations studied the first steps of CIGB552 aggregation under physiological ionic strength conditions (NaCl 150 mM), showing that peptide oligomers, from dimers to tetramers, are preferentially formed in this environment. Interestingly, cell viability assays performed on H‐460 cell lines indicate a major antiproliferative activity of the peptide in its therapeutic formulation with respect to the peptide aqueous solution. Abstract : Therapeutic formulation deeply affects the aggregation properties and morphology of an anticancer peptide, as shown by spectroscopic measurements, atomic force microscopy imaging and Molecular Dynamics simulations.